Effect of sirolimus on renal ischaemia/reperfusion injury in normotensive and hypertensive rats - Viklický, Ondrej; Bohmová, Radka; Ouyang, Nengtai; Honsová, Eva; Lodererová, Alena; Mandys, Václav; Vítko, Stefan; Lutz, Jens; Heemann, Uwe W (Transplant international, 2004)
Renal ischaemia/reperfusion (I/R) injury and hypertension represent major alloantigen-independent factors contributing to the development of chronic allograft nephropathy of renal allografts. In the present study, we investigated the effect of the anti-proliferative immunosuppressant, sirolimus (SIR), in a model of accelerated renal injury in hypertensive transgenic rats (TGRs). Twenty anaesthetized uninephrectomized TGRs with renin overproduction [TGR(mREN2)27] and 20 normotensive Han SD (SD) rats as genetic controls had their renal pedicles clipped for 45 min and were subsequently treated with either SIR (0.5 mg/kg per day, orally) or placebo ( n=10 in each group) for 16 weeks, after which time the kidneys were harvested for morphological and immunohistochemical analysis. High-renin hypertension aggravated the functional and structural changes induced by I/R in SD animals: both SIR-treated and untreated TGRs exhibited significantly greater proteinuria and suffered from more severe glomerulosclerosis ( P<0.01) and vasculopathy ( P<0.01), as well as compensatory renal hypertrophy ( P<0.01) and tissue TGF-beta1 expression, than both normotensive SD groups ( P<0.01). SIR-treated SD rats showed reduced proteinuria ( P<0.01), glomerulosclerosis ( P<0.01), and TGF-beta1 expression in the glomerular epithelium and proximal tubuli ( P<0.05) compared with placebo-treated SD rats. SIR-treated TGRs had significantly lower proteinuria at week 4 after I/R ( P<0.01) than placebo-treated TGRs, but there were no significant differences thereafter. Morphological patterns were similar in treated and untreated TGRs at week 16. High-renin-induced hypertension aggravated the renal injury induced by I/R. Sirolimus treatment ameliorated some late functional and morphological changes induced by I/R injury in hypertensive TGRs but, particularly, in normotensive SD rats.
Keywords: Renal Circulation; Urea; krevní tlak; reperfuzní poškození; Kidney Function Tests; Immunosuppressive Agents; Sirolimus; sirolimus; Animals, Genetically Modified; Rats, Inbred SHR; Renin; Blood Pressure; potkani inbrední SHR; krysa rodu Rattus; potkani Sprague-Dawley; Reperfusion Injury; vyšetření funkce ledvin; myši; Mice; renální oběh; geneticky modifikovaná zvířata; Rats, Sprague-Dawley; mužské pohlaví; zvířata; imunosupresiva; močovina; Rats; kreatinin; Animals; renin; Male; Creatinine